Ventilation during cardiopulmonary bypass did not attenuate inflammatory response or affect postoperative outcomes - Durukan, Ahmet Baris (Clinics Cardive Publishing, 2013)
INTRODUCTION: Cardiopulmonary bypass causes a series of inflammatory events that have adverse effects on the outcome. The release of cytokines, including interleukins, plays a key role in the pathophysiology of the process. Simultaneously, cessation of ventilation and pulmonary blood flow contribute to ischaemia–reperfusion injury in the lungs when reperfusion is maintained. Collapse of the lungs during cardiopulmonary bypass leads to postoperative atelectasis, which correlates with the amount of intrapulmonary shunt. Atelectasis also causes post-perfusion lung injury. In this study, we aimed to document the effects of continued low-frequency ventilation on the inflammatory response following cardiopulmonary bypass and on outcomes, particularly pulmonary function. METHODS: Fifty-nine patients subjected to elective coronary bypass surgery were prospectively randomised to two groups, continuous ventilation (5 ml/kg tidal volume, 5/min frequency, zero end-expiratory pressure) and no ventilation, during cardiopulmonary bypass. Serum interleukins 6, 8 and 10 (as inflammatory markers), and serum lactate (as a marker for pulmonary injury) levels were studied, and alveolar–arterial oxygen gradient measurements were made after the induction of anaesthesia, and immediately, one and six hours after the discontinuation of cardiopulmonary bypass. RESULTS: There were 29 patients in the non-ventilated and 30 in the continuously ventilated groups. The pre-operative demographics and intra-operative characteristics of the patients were comparable. The serum levels of interleukin 6 (IL-6) increased with time, and levels were higher in the non-ventilated group only immediately after discontinuation of cardiopulmonary bypass. IL-8 levels significantly increased only in the non-ventilated group, but the levels did not differ between the groups. Serum levels of IL-10 and lactate also increased with time, and levels of both were higher in the non-ventilated group only immediately after the discontinuation of cardiopulmonary bypass. Alveolar–arterial oxygen gradient measurements were higher in the non-ventilated group, except for six hours after the discontinuation of cardiopulmonary bypass. The intubation time, length of stay in intensive care unit and hospital, postoperative adverse events and mortality rates were not different between the groups. CONCLUSION: Despite higher cytokine and lactate levels and alveolar–arterial oxygen gradients in specific time periods, an attenuation in the inflammatory response following cardiopulmonary bypass due to low-frequency, low-tidal volume ventilation could not be documented. Clinical parameters concerning pulmonary and other major system functions and occurrence of postoperative adverse events were not affected by continuous ventilation.